EPIDEMICITY OF POLIOMYELITIS—Possible Role of Seasonal Variation in Food Quality - SPETZ, M (California medicine, 1954)
Seasonal variations occur in the phosphate, phospholipid and protein content of foods. The lower content occurs in the dry season. This is most often in the summer and fall months, which is the usual time of year for epidemics of poliomyelitis. Question is raised as to whether epidemics of poliomyelitis are a consequence of the host-virus balance being shifted in favor of the virus during this season because of the lower nourishing power of foods common to the daily diet.